The baby-sitters club. 9, Claudia and the new girl - Epstein, Gabriela; Martin, Ann M., 1955- (New York : Graphix, 2021)
Ashley thinks Claudia has artistic talent and should spend more time on her 'calling' and forget about the Babysitters Club. Claudia has to decide between the Baby-sitters Club and Ashley.
Based on: Claudia and the new girl / Ann M. Martin.
2.6
3-6
GN360L
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc -- Juvenile fiction; Babysitters -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Clubs -- Comic books, strips, etc -- Juvenile fiction; Babysitters Club (Imaginary organization) -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Clubs -- Fiction; Cartoons and comics; Graphic novels; Comics (Graphic works)